Cover Feature: Towards Reverse Transcription with an Expanded Genetic Alphabet (ChemBioChem 13/2019). (13th June 2019) - Eggert, Frank; Kurscheidt, Katharina; Hoffmann, Eva; Kath‐Schorr, Stephanie
Abstract : The cover feature picture shows the unnatural hydrophobic base pair TPT3:NaM during reverse transcription, with rTPT3 in the RNA template strand and an incoming dNaM triphosphate. Four retroviral derived reverse transcriptases, as well as a mutant of Taq DNA polymerase with reverse transcriptase activity, are questioned for their ability to handle an expanded genetic alphabet. More information can be found in the communication by S. Kath‐Schorr et al. onpage 1642 in Issue 13, 2019 (DOI:10.1002/cbic.201800808 ). (Background structure for illustration only: XMRV reverse transcriptase, PDB ID: 4HKQ).